PENGARUH MANAJEMEN LABA DAN MEDIA EXPOSURE TERHADAP CARBON EMISSION DISCLOSURE DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Tsuroyya, Yasmin Yumnaa; Ratmono, Dwi (Diponegoro Journal of Accounting, 2024)
This research aims to obtain empirical evidence regarding the influence of earnings management and media exposure on carbon emissions disclosure (CED) and the role of Corporate Governance (CG) proxies in moderating this influence. The CG proxies used include the number of members of the board of commissioners, the proportion of independent board of commissioners, the frequency of audit committee meetings, and the proportion of the audit committee with financial expertise. This research also uses several control variables including company size and leverage.The samples used in this research were taken using a purposive sampling method totaling 276 samples from 109 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019-2022. The analytical methods used are linear regression analysis and moderated regression analysis (MRA) which were tested using the EViews 12 application.The results of this study indicate that earnings management has no influence on carbon emissions disclosure, while media exposure was found to have a positive influence on carbon emissions disclosure. The CG proxy in the form of the frequency of audit committee meetings is able to weaken the negative influence of earnings management on carbon emissions disclosure.